In a world in shadows and flames scientists and laypeople need better understanding of how science works - Albuquerque, Ulysses; N. El-Hani, Charbel (Ethnobiology and Conservation, 2020)
Major events, such as pandemics and war, generate great public interest in science, as in the current moment in which we live. We argue, however, that this interest operates through historical pulses and that it does not lead to an increase in scientific literacy in society in general and even among the scientists themselves.